A UPLC–MS/MS method for comparative pharmacokinetics study of morusin and morin in normal and diabetic rats. (21st March 2019) - Liu, Jia; Mu, Yanling; Xiong, Shan; Sun, Peilu; Deng, Zhipeng
Abstract: The aim of this study was to establish and validate a rapid, selective and reliable ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) for simultaneous quantitations of morin and morusin, and to investigate their pharmacokinetics difference between normal and diabetic rats after oral administration. Plasma samples were pretreated via protein precipitation with acetonitrile. Genkwanin was used as internal standard (IS). Analytes and IS were separated on a Thermo Hypersil Gold C18 column (50 × 4.6 mm, 3 μm) using gradient elution. The mobile phase consisted of acetonitrile and 0.1% formic acid in water at a flow rate of 0.5 mL/min. Mass spectrometry detection was carried out by means of negative electrospray ionization source and multipe‐reaction monitoring mode. The transitions of m/z 300.9 → 151.2 for morin, m/z 419.2 → 297.1 for morusin and m/z 283.1 → 268.2 for IS were chosen for quantification. Calibration curves were linear in the range of 1.01–504.2 ng/mL ( r 2  ≥ 0.99) for morin and 1.02–522.3 ng/mL ( r 2  ≥ 0.99) for morusin. The lower limit of quantification was 1.02 ng/mL for morin and 1.05 ng/mL for morusin. The extraction recovery was >85.1% for each analyte. No obvious matrix effect was observed under the present UPLC–MS/MS conditions during all of the bioanalysis. The stability study demonstrated that morin and morusin remained stable during the whole analytical procedure. The method was successfully applied to support the pharmacokinetic comparisons of morin and morusin between normal and diabetic rats.